Epilepsy: Awareness Strategy - Rahman, Sayed Wahidur (Journal of Chittagong Medical College Teachers' Association, 2010)
DOI: 10.3329/jcmcta.v20i2.5626 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):48-49